2011
DOI: 10.1161/atvbaha.111.226365
|View full text |Cite
|
Sign up to set email alerts
|

An Increased Burden of Common and Rare Lipid-Associated Risk Alleles Contributes to the Phenotypic Spectrum of Hypertriglyceridemia

Abstract: Objective Earlier studies have suggested that a common genetic architecture underlies the clinically heterogeneous polygenic Fredrickson hyperlipoproteinemia (HLP) phenotypes defined by hypertriglyceridemia (HTG). Here, we comprehensively analyzed 504 HLP-HTG patients and 1213 normotriglyceridemic controls and confirmed that a spectrum of common and rare lipid-associated variants underlies this heterogeneity. Methods and Results First, we demonstrated that genetic determinants of plasma lipids and lipoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 29 publications
1
68
0
Order By: Relevance
“…A previous study in a population with a more severe hypertriglyceridemia than ours had shown that genetic variants in 7 loci and clinical variables explained ≈40% of triglyceride variation. 29,30 We found a similar percentage in our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A previous study in a population with a more severe hypertriglyceridemia than ours had shown that genetic variants in 7 loci and clinical variables explained ≈40% of triglyceride variation. 29,30 We found a similar percentage in our study.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast with a previous study, 29,30 we have considered mild hypertriglyceridemia (triglyceride levels >200 mg/dL) to include isolated hypertriglyceridemia and FCHL. Johansen et al 29 studied 504 participants with triglycerides >500 mg/dL.…”
Section: Discussionmentioning
confidence: 99%
“…Familial should not be thought of as synonymous with monogenic; most cases of hypertriglyceridaemia are familial or inherited, but they are not monogenic. 35,36 …”
Section: Complex Genetic Basis For Hypertriglyceridaemiamentioning
confidence: 99%
“…A genetic risk score, constructed by unweighted tallying of carrier status for triglyceride-raising alleles at the 32 triglyceride-associated loci, was on average higher for patients with hypertriglyceridaemia than for healthy controls (figure 2). 36,51 Thus, as for mutation-negative patients with familial hyper-cholesterolaemia and LDL-cholesterol raising variants, 41 an increased burden of triglyceride-raising alleles contributes to hypertriglyceridaemia susceptibility. 48,49 …”
Section: Multigenic Hypertriglyceridaemiamentioning
confidence: 99%
“…67,304 Moderate elevation of TG levels (between 2.0-10.0 mmol/L) is caused by the polygenic effect of multiple genes influencing both VLDL production and removal. In CVD prevention, polygenic moderate TG elevation is to be considered.…”
Section: Genetic Causes Of Hypertriglyceridaemiamentioning
confidence: 99%